"Trotz allem glaube ich an das Gute im Menschen". Das Tagebuch der Anne Frank und seine Rezeption in der Bundesrepublik Deutschland - Heimsath, Katja 1976- (Hamburger Historische Forschungen, 2013)
The Jewish girl Anne Frank left behind an impressive and comprehensive testimony of the National Socialist atrocities in the "Third Reich". Her diary is the subject of this thesis. The volume deals with the comprehensive history of the reception of the book which is the most widely read in Germany besides the bibleIn the years 1950 to 1989 Anne Frank's diary, its later staging as a play and the filming gave the German Federal Republican society the impetus to recall, remind, and deal with the Nazi past. The way in which Anne Frank's diary is received in the Federal Republic of Germany directly interacts with political events and revolves around a variety of interpretative patterns